Free and open Indo-Pacific strategy outlook - Arase, David (Trends in Southeast Asia, 2019)
The United States launched a new Free and Open Indo-Pacific (FOIP) strategy in late 2017 after reluctantly concluding that its patient effort to engage and socialize China to the rules-based order since 1972 had failed. China's behaviour since 2009 convinced the United States that China is a revisionist power seeking to impose an authoritarian model of governance in Asia which, if successful, would end the rules-based order in the Indo-Pacific as well as endanger US security and vital trade interests. The new US FOIP strategy initiative seeks to engage like-minded nations in economic, security.